The The Pharmacokinetics of Single-Inhaler Triple Therapy: A Systematic Review: Farmakokinetika Inhaler Tunggal Tiga Komponen: Ulasan Sistematis - Sang Ayu Made Arenawati; I Nyoman Dwika Dharmanta; Made Ary Sarasmita; Eka Indra Setyawan; Luh Putu Mirah Kusuma Dewi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2026)
Background: The integration of inhaled corticosteroids, long-acting -agonists, and long-acting muscarinic antagonists into a fixed-dose Single Inhaler Triple Therapy (SITT) represents a pivotal strategy for managing chronic obstructive pulmonary disease (COPD) in patients with persistent symptomatology or frequent exacerbations. Despite the proven clinical efficacy of SITT, data regarding its pharmacokinetic properties across both healthy volunteers and the COPD population appear disjointed, warranting a comprehensive synthesis. Methods: We executed a systematic review following the PRISMA 2020 framework. A rigorous search of electronic databases was undertaken to retrieve clinical and population pharmacokinetic trials examining SITT. Articles were screened against specific inclusion criteria, and methodological quality was scrutinised using standard risk-of-bias instruments. Data synthesis was performed narratively, prioritizing essential pharmacokinetic indicators. Results: The review consolidated data on key metrics, specifically peak plasma concentrations, total systemic exposure, and time to peak. The analysis revealed that systemic bioavailability of the triple combination components is bioequivalent to that of their respective mono- or dual-therapy formulations. Furthermore, no significant drug accumulation was detected following multiple doses. Variations in pharmacokinetic behavior were predominantly linked to patient demographics, disease severity, and inhaler handling proficiency. Conclusion: SITT exhibits a consistent and predictable pharmacokinetic profile characterized by low systemic exposure in both healthy individuals and patients with COPD. These insights reinforce the pharmacological stability and therapeutic viability of single-inhaler regimens in clinical practice.